Analysis of the cultural, identity and social impacts of the colonialism on the representations of male and female roles in the novel "The Joys of Maternity" (TEL Tempo, Espaço e Linguagem, 2022)
In this article, we intend to analyze some aspects inherent to the novel “The Joys of Maternity”, by Buchi Emecheta, namely, the way in which British colonialism influences the transformation of some characters regarding their identities and the relationships between Nigerian population and society in terms of literacy, mainly that of reexistence, establishing an uprooting of their idiosyncrasies linked to tribal life in Ibuza. As a theoretical approach, Anne McClintock's concepts about European colonialism will be used in the context of decolonial readings, as well as the biases of Stuart Hall and James Paul Gee about the construction of the individual's identity. Regarding literacy, Angela B. Kleiman and Juliana A. Assis will be used to establish the sociocultural perspectives of writing in the formal and informal context permeated by reexistence.